Performance study of the coexistence of Wireless Sensor Networks (WSN) and Wireless Local Area Networks (WLAN) / Muhammad Adib Haron … [et al.] - Haron, Muhammad Adib; Jusoh, Mohamad Huzaimy; Abdul Aziz, Noor Hafizah; W. Muhamad, Wan Norsyafizan (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2008)
Wireless sensor networks (WSN) are composed of large numbers of tiny networked devices, which are called sensor nodes. Current WSN are assigned to a fixed spectrum assignment policy by The Malaysian Communications and Multimedia Commission (MCMC). Large portion of the assigned spectrum is used by licensed user in particular geographic areas. Only a few, small, unlicensed bands were left open for anyone to use as long as they followed certain power regulations. With the recent demand in personal wireless technologies, these unlicensed bands have become crowded with everything from wireless networks to digital cordless phones. The basic idea to solve this overcrowding in unlicensed band is to manage the available bands through spectrum sharing. Spectrum sharing is one of the dynamic spectrum access (DSA) technique used to optimize spectrum utilization by suggesting an interference temperature model (lTM) at the data link layer for controlling spectrum use. This scheme will be deployed by combining the interference temperature multiple accesses (lTMA) on top of existing slotted/unslotted CSMAICA. To implement WSN integrated with cognitive radio techno 10gy, a new algorithm that provides access mechanism is needed to interactively working with sensor nodes hardware. This project proposes a special state machine of lIMA, a novel that characterizes both interference and noise with single parameters in WSN application. Measure the current interference temperature (T[) before each transmission. It can then determine what transmit power and data rate that should be used to achieve desired capacity without violating an interference temperature limit (TL) at other transceiver.